PENGARUH METODE ROLE PLAYING BERBANTUAN SUMBER BELAJAR LINGKUNGAN SEKITAR TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN IPAS SISWA UPTD SDN 18 RIAU SILIP - Nando Zali Alridho; Maulina Hendrik; Yurdayanti (STKIP Subang, 2026)
One of the main problems raised by this study is the low critical thinking ability of students while studying in science. Other problems are the lack of various teaching methods and the lack of use of open resources from the surrounding environment. The aim is to determine whether the role-playing method assisted by learning resources from the surrounding environment can affect students' critical thinking ability. The quantitative method used, and the experimental design is One Group Pretest-Posttest Design. 17 fourth-grade students from UPTD SD Negeri 18 Riau Silip were one of the subjects. The collected essay questions were used to test critical thinking ability. The Shapiro-Wilk normality test and sequential sample t-test were then used to examine the data. The results showed an increase in the average score from 50 in the pretest to 78.2 in the posttest. With a hypothesized p-value of 17.638, which is greater than the t-table of 2.120, and a p-value of 0.001 which is less than 0.05, the data were found to be normally distributed. The pretest significance value was 0.237 and the posttest significance value was 0.210, both of which were greater than 0.05. Therefore, it can be concluded that students' critical thinking skills in science learning are truly influenced by their roles and learning resources from their environment.